Classification of Subcellular Location by Comparative Proteomic Analysis of Native and Density-shifted Lysosomes - Della Valle, Maria Cecilia (The American Society for Biochemistry and Molecular Biology, 2011)
One approach to the functional characterization of the lysosome lies in the use of proteomic methods to identify proteins in subcellular fractions enriched for this organelle. However, distinguishing between true lysosomal residents and proteins from other cofractionating organelles is challenging. To this end, we implemented a quantitative mass spectrometry approach based on the selective decrease in the buoyant density of liver lysosomes that occurs when animals are treated with Triton-WR1339. Liver lysosome-enriched preparations from control and treated rats were fractionated by isopycnic sucrose density gradient centrifugation. Tryptic peptides derived from gradient fractions were reacted with isobaric tag for relative and absolute quantitation eight-plex labeling reagents and analyzed by two-dimensional liquid chromatography matrix-assisted laser desorption ionization time-of-flight MS. Reporter ion intensities were used to generate relative protein distribution profiles across both types of gradients. A distribution index was calculated for each identified protein and used to determine a probability of lysosomal residence by quadratic discriminant analysis. This analysis suggests that several proteins assigned to the lysosome in other proteomics studies are not true lysosomal residents. Conversely, results support lysosomal residency for other proteins that are either not or only tentatively assigned to this location. The density shift for two proteins, Cu/Zn superoxide dismutase and ATP-binding cassette subfamily B (MDR/TAP) member 6, was corroborated by quantitative Western blotting. Additional balance sheet analyses on differential centrifugation fractions revealed that Cu/Zn superoxide dismutase is predominantly cytosolic with a secondary lysosomal localization whereas ATP-binding cassette subfamily B (MDR/TAP) member 6 is predominantly lysosomal. These results establish a quantitative mass spectrometric/subcellular fractionation approach for identification of lysosomal proteins and underscore the necessity of balance sheet analysis for localization studies.